Ophthalmic Wearable Devices for Color Blindness Management. Issue 8 (27th May 2020) - Salih, Ahmed E.; Elsherif, Mohamed; Ali, Murad; Vahdati, Nader; Yetisen, Ali K.; Butt, Haider
Abstract: Color vision deficiency (CVD) or color blindness is an ocular disorder that hinders the patients from distinguishing shades of certain colors. Color blind patients are often not considered for critical occupations (e.g., military, police) and cannot differentiate colors in public places or media (i.e., watching TV). The most common form of color blindness is red‐green, which is a result of either a missing or defective red or green photoreceptor cone. Since no cure for this disorder exists, sufferers opt for methods to enhance their color perception. The products and methods that have been developed to aid CVD patients are discussed. These technologies include contemporary work on gene therapy, tinted glasses, lenses, optoelectronic glasses, and advanced features developed on smartphones and computers. Among these wearables, tinted glasses, developed by companies such as Enchroma, are the most widely used by CVD patients. Abstract : Commercial and research‐based products that have been developed to aid color blind patients are reviewed. These technologies include contemporary work on gene therapy, tinted glasses, contact lenses, optoelectronic glasses, and advanced features on smartphones and computers. Among these wearables, tinted glasses, developed by companies such as Enchroma and VINO/O2Amp, are the most widely used by color blind patients.